A task and role-based access control model in a computer-supported cooperative design system. (2017) - Ai, Fei; Zhang, Ping; Du, Guanglong
To properly reflect the requirements of a computer-supported cooperative design system (CSCD), a task and role-based access control model (T&RBAC) is proposed. The T&RBAC model extends the T-RBAC model, defines the key elements, and the relationships of the elements. The concept of a 'usergroup' is introduced in the model to simplify user and authorisation management. Additionally, the classification of the role and task is presented according to the requirements of the CSCD's access control policy, and supports the permissions to be assigned to both the tasks and roles, and hence realises the active and passive access control policies. Finally, the T&RBAC model is validated in the CSCD system.